Educational Provision for the Local Arts and Culture Following the Educational Concept by Her Royal Highness Princess Maha Chakri Sirindhorn: A Case Study of Border Pa-trol Police Schools - Bangchuad, Doungkamol; Hongwityakorn, Ubonwan; Akkaraputtapong, Panya; Chobphon, Peson; Srinual, Supachai (Journal of International Studies, Prince of Songkla University, 2024)
The objectives of this research were to 1) analyze concepts, practices, and educational management for the transmission of local arts and culture at border patrol police schools and 2) to propose the education management guidelines to carry on the local arts and culture at border patrol police schools thought by Her Royal Highness Princess Maha Chakri Sirindhorn. The research methodology included documentary research, interviews from eight border patrol schools and learning center and focus group discussion. The results found that there were different educational management strategies depending on each school’s context. Most schools focused on local curriculum creation, which integrates with other subjects or activities supported by the Border Patrol Police Division, local government agencies, private sector companies, and the community to transmit their own culture and increase income. The educational management is the role and duty of Border Patrol Police Headquarters to arrange continuous teacher development system for both knowledge and teaching skill, incentive system, and following and supporting these systems based on national education indicators and children youth in the wilderness area development plan of Her Royal Highness Princess Maha Chakri Sirindhorn, including budgeting and specific practical guidance for teachers. School has a role and duty which involved the sharing of teaching ideas to integrate art and culture with other subjects, establishing alumni associations and encouraging sharing among social networks is necessary.